Pengaruh Religiositas terhadap Keputusan Pembelian Pakaian Muslimah - Dessy Trimulyani; Hendro Lisa; Ferdinan Ferdinan (AL-Muqayyad, 2021)
Starting from the phenomenon occurred especially among Muslim women who were very concerned with fashion issues. Many of them did not know the function of the clothes they wear, and how Islam arranges the clothes. The purpose of this study was to determine the influence of religiosity on the decision of purchasing Muslim clothes in Tembilahan District. This was quantitative research by simple linear regression method analysis. The results showed that the T count was bigger than the T table. The T table was 12,763>2,024 and sig. 0.000 <0.05 means Ha was accepted, and Ho was rejected. The contribution of religiosity to the decision toward purchasing Muslim clothing by looking at the results of the R Square was 81.1%, while the remaining 18.9% influenced by other factors outside of the researcher's discussion.